Five Nights at Freddy's : Fazbear Frights - Vol 3 Vol. 3 - Cawthon, Scott, 1971-; Waggener, Andrea Rains, 1960-; Parra, Kelly; Hastings, Chris, 1983-; Esmeralda, Didi; MacPherson, Coryn; Camero, Diana; Sawyer, Benjamin; Duarte, Gonzalo (Colorist); Lai, Judy; Esposito, Taylor (New York, NY : Graphix, an imprint of Scholastic, 2023)
In this volume, three stories from the New York Times bestselling series Five Nights at Freddys: Fazbear Frights come to life in delightfully horrifying comics. Readers beware: This collection of terrifying tales is enough to unsettle even the most hardened Five Nights at Freddys fans . . .
illustrated by Diana Camero ; colors by Judy Lai ; letters by Taylor Esposito.
Rated Teen: Ages 12 and up.
Keywords: Robotics -- Comic books, strips, etc; Robots -- Comic books, strips, etc; Pizzerias -- Comic books, strips, etc; Survival -- Comic books, strips, etc; Robots -- Fiction; Pizzerias -- Fiction; Survival -- Fiction; Graphic novels; Horror comics; Comics adaptations; Graphic novel adaptations; Comics (Graphic works)